SiRNA Delivery: A Fluorinated Bola‐Amphiphilic Dendrimer for On‐Demand Delivery of siRNA, via Specific Response to Reactive Oxygen Species (Adv. Funct. Mater. 47/2016). (December 2016) - Liu, Xiaoxuan; Wang, Yang; Chen, Chao; Tintaru, Aura; Cao, Yu; Liu, Juan; Ziarelli, Fabio; Tang, Jingjie; Guo, Hongbo; Rosas, Roseline; Giorgio, Suzanne; Charles, Laurence; et al.
Abstract : A fluorinated bola‐amphiphilic dendrimer, sensitive to the reactive oxygen species, and its application in specific delivery of small interfering RNA in cancer cells, is reported by L. Peng and co‐workers on page 8594. The dendrimer combines both lipid and dendrimer delivery advantages along with fluorine tags enabling 19 F NMR studies on the delivery process, constituting a promising vector for on‐demand stimulus‐responsive delivery.